Genetic markers for massively parallel sequencing in forensics. (December 2015) - Kidd, Kenneth K.; Speed, William C.; Wootton, Sharon; Lagace, Robert; Langit, Reina; Haigh, Eva; Chang, Joseph; Pakstis, Andrew J.
Abstract: Massively parallel sequencing (MPS, aka NGS) is revolutionizing the field of forensics. Existing forensic short tandem repeat polymorphisms (STRPs) are more informative when typed by MPS. MPS also allows STRPs and forensic SNP panels to be multiplexed to add information, on ancestry and phenotype, to the identification information from STRPs. MPS also makes possible microhaplotypes: small segments of DNA (<300 bp) with two or more single nucleotide polymorphisms (SNPs) unambiguously defining three or more haplotypes. Because a single sequence read can cover the expanse of the microhaplotype, these loci become phase-known codominant systems. The multiple alleles (haplotypes) provide much more information than a single SNP for the same effort. Data now available on 129 loci characterized on 55 populations from around the globe demonstrate that the majority of these microhaplotypes appear to be useful in forensics for individual identification, ancestry inference, estimating relationships, and especially deconvoluting mixtures.